Experimental investigation on the resistivity and mechanical properties of high-resistance cement-based grouting materials for mining - Bin Xu; Bin Xu; Bin Xu; Rongrong Qi; Shuning Dong; Zhenxue Dai; Shangxian Yin; Hewen Ma; Cen Zhong (Frontiers in Earth Science)
The electrical characteristics of cement-based grouting materials are the foundation for implementing geophysical electrical exploration in coal mine grouting engineering. However, the preparation methods for high-resistivity grouting materials, which act as “contrast agents” in geophysical surveys, remain unclear due to the multiple influencing factors of resistivity. To address this, resistivity experiments were conducted using a self-developed apparatus to investigate the effects of curing age, admixture type, and dosage on the resistivity characteristics of grouting materials. This led to identifying optimal mix proportions for conventional cement-based high-resistivity grouting materials. Concurrently, mechanical strength tests were performed to analyze the impact of admixture dosage and curing age on compressive strength. The results indicate that the resistivity enhancement effects of four common cement additives can be ranked as follows: pyrophyllite powder >polyvinyl alcohol > air-entraining agent > fly ash. Considering both resistivity increase and mechanical strength, talc powder and polyvinyl alcohol emerge as viable candidates for use as additives in cement-based high-resistivity grouting materials. Specifically, with a talc powder dosage of 15%, the electrical resistivity of the grouted body after 28 days reached 4,966.7 Ω m, which is 119.1 times that of the control group (41.7 Ω m). Similarly, with a polyvinyl alcohol dosage of 1%, the resistivity reached 7,070.6 Ω m, which is 169.6 times that of the control group. These findings provide critical insights for developing high resistivity grouting materials with dual functionality as geophysical contrast agents and structural reinforcements.